An industrial quality control study on C.C. Lopez Enterprises - Costales, Franz Josef; Mallari, Pericles II; Velasco, Gelvin (Quezon City College of Engineering, University of the Philippines Diliman, 2006)
In this industrial quality control study, the proponents aimed to determine whether the production process of C.C. Lopez Enterprises is in statistical quality control and find assignable causes for lots that do not seem to be in control. Additionally, the proponents were tasked to determine whether the plan of management for expansion of the production facility is viable. Over the course of the study, it was determined that sewing errors were the major cause of nonconforming units, accounting for almost 70% of all defective units. As such, the statistical process control study was aimed at finding the causes of these sewing errors, and which sewers, if any were accountable for the bulk of the errors. Given the circumstances, the proponents found five main aspects of the production process that need to be addressed. The first of these is the layout of the facility. The limited floor area of the shop leads to much backtracking of work, and thus delays in production. This problem could be solved by expanding the work area and hopefully relocate to a new production facility. Management has taken the initiative in this regard and has plans for future expansion. Documentation of the process was also lacking. The skill levels of the workers were not considered in assigning job orders, scheduling of the orders to be processed are seemingly random, and no performance records for the employees exist. In line with this, the proponents suggest that a logbook of all job orders, as well as incoming and outbound deliveries be kept to improve the scheduling of lots to be processed. Additionally, a performance record of the employees should be kept, to ensure that the good performers are rewarded and to minimize the loses due to unsatisfactory performance. Finally, the proponents believe that the expansion program conceived by management is beneficial to the company, as the overall capacity for production is increased and losses due to rework, overtime, and subcontracting are minimized. Additionally, the short payback period of years required for the investment indicate that the company could immediately recoup their loss.
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial quality control.
Keywords: Ready-to-wear clothing industry; Quality control